1997
DOI: 10.1002/bjs.1800840212
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen levels correlate with stage of disease in patients with oesophageal cancer

Abstract: This study demonstrates a stage-dependent phenomenon of hyperfibrinogenaemia in association with oesophageal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…Fibrinogen is primarily produced in the liver and is converted by the proteolytic action of thrombin. The elevated plasma fibrinogen levels reflect the status of tumor cell-host interactions, and the cellular interactions may be serving as an important contributing factor in cancer development including cell migration, promotion, and inflammatory mediators 47, 48. Secondly, Evaluated CRP and fibrinogen are indicators of tumor-associated inflammatory response, which is companied by up-regulation of cytokines and inflammatory mediators, inhibition of apoptosis, induction of angiogenesis, stimulation of DNA damage and immunosuppression and remodelling of the extracellular matrix, hence promoting tumor growth and metastasis 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen is primarily produced in the liver and is converted by the proteolytic action of thrombin. The elevated plasma fibrinogen levels reflect the status of tumor cell-host interactions, and the cellular interactions may be serving as an important contributing factor in cancer development including cell migration, promotion, and inflammatory mediators 47, 48. Secondly, Evaluated CRP and fibrinogen are indicators of tumor-associated inflammatory response, which is companied by up-regulation of cytokines and inflammatory mediators, inhibition of apoptosis, induction of angiogenesis, stimulation of DNA damage and immunosuppression and remodelling of the extracellular matrix, hence promoting tumor growth and metastasis 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that raised levels of systemic inflammatory markers are associated with poorer survival in patients with cancer. Peripheral blood‐derived inflammation markers including the neutrophil : lymphocyte ratio (NLR), platelet : lymphocyte ratio (PLR), Glasgow Prognostic Score (GPS) and fibrinogen levels have been proposed as potential markers of prognosis in oesophageal cancer. The majority of these studies, however, focused on squamous cell carcinoma of the oesophagus, and thus it is difficult to draw any valid conclusions for a Western population.…”
Section: Introductionmentioning
confidence: 99%
“…(7) In addition to its well-known roles in blood coagulation, recent studies have shown that fibrinogen plays important roles in a variety of processes, which include cell-to-cell interactions, inflammation, and cancer progression. (7-9) Elevated fibrinogen can enhance augment lymphatic and hematogeneous metastasis of advanced gastric cancer, which is major determinant of the prognosis in T2 gastric cancer. (10) In a previous study, we found that pre-operative plasma fibrinogen level is a useful marker of extent of tumor progression in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%